Separation and investigation of structure-mobility relationships of insect oostatic peptides by capillary zone electrophoresis - Solínová, Veronika; Kasicka, Václav; Koval, Dusan; Hlavácek, Jan (Electrophoresis, 2004)
Capillary zone electrophoresis (CZE) has been applied to qualitative analysis, separation, and physicochemical characterization of synthetic insect oostatic peptides (IOPs) and their derivatives and fragments. Series of homologous IOPs were separated in three acidic background electrolytes (BGEs; pH 2.25, 2.30, 2.40) and an alkaline BGE (pH 8.1). Best separation was achieved in acid BGE composed of 100 mM H3PO4, 50 mM Tris, pH 2.25. The effective electrophoretic mobilities, mu(ep), of all IOPs in four BGEs were determined and several semiempirical models correlating effective mobility with charge-to-size ratio (mu(ep) versus q/Mr k) were tested to describe the migration behavior of IOP in CZE. None of models was found to be unambiguously applicable for the whole set of 20 IOPs differing in size (dipeptide - decapeptide) and charge (-2 to +0.77 elementary charges). However, a high coefficient of correlation, 0.9993, was found for the subset of homologous series of IOPs with decreasing number of proline residues at C-terminus, H-Tyr-Asp-Pro-Ala-Prox-OH, x = 6 - 0, for the dependence of mu(ep) on q/Mr k with k = 0.5 for IOPs as anions in alkaline BGE and with k = 2/3 for IOPs as cations in optimized acidic Tris-phosphate BGE. From these dependences the probable structure of IOPs in solution could be predicted.
Keywords: Oligopeptides; algoritmy; Animals; zvířata; teoretické modely; oligopeptidy; hmyz; Electrophoresis, Capillary; Models, Theoretical; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Insecta; elektroforéza kapilární; Algorithms